A systematic review of the physical and chemical characteristics of pollutants from biomass burning and combustion of fossil fuels and health effects in Brazil - Beatriz Fátima Alves de Oliveira; Eliane Ignotti; Sandra S. Hacon (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to carry out a review of scientific literature published in Brazil between 2000 and 2009 on the characteristics of air pollutants from different emission sources, especially particulate matter (PM) and its effects on respiratory health. Using electronic databases, a systematic literature review was performed of all research related to air pollutant emissions. Publications were analyzed to identify the physical and chemical characteristics of pollutants from different emission sources and their related effects on the respiratory system. The PM2.5 is composed predominantly of organic compounds with 20% of inorganic elements. Higher concentrations of metals were detected in metropolitan areas than in biomass burning regions. The relative risk of hospital admissions due to respiratory diseases in children was higher than in the elderly population. The results of studies of health effects of air pollution are specific to the region where the emissions occurred and should not be used to depict the situation in other areas with different emission sources.